2022
DOI: 10.1097/mrr.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

Residual and sound limb hip strength distinguish between sedentary and nonsedentary adults with transtibial amputation

Abstract: Following a transtibial amputation (TTA), physical activity has known benefits for health and quality of life. Adults post-TTA, however, demonstrate reduced physical activity, predisposing them to adverse health outcomes. Identifying adults at the risk of sedentarism post-TTA via commonly used, objective clinical measures may enhance clinical decisions, including prosthesis prescription. The study’s purpose was to determine whether residual and sound limb hip strength distinguishes between sedentary and nonsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Direct comparisons across the literature are however limited by the substantial methodological variation across studies. Notable variations in data collection and analysis throughout the literature include testing posture (e.g., supine, sitting, or standing) and joint angle [ 5 , 21 , 23 ], testing equipment (i.e., computerized versus handheld dynamometer) [ 11 13 , 19 , 20 ], mode of muscle action (i.e., isometric versus isokinetic) [ 5 , 8 , 11 , 13 , 23 ], whether the prosthesis is worn [ 10 12 , 21 , 23 ] or removed [ 5 , 8 , 9 , 13 , 19 , 24 , 28 , 31 ] while testing the residual limb, gravity compensation, familiarization (i.e., number of trials) [ 55 ], and normalization for confounding anthropometric variables [ 22 ]. The adoption of standardized methods for data collection, processing, and reporting of strength-related outcomes in LLP users would enable the comparison and aggregation of data across studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct comparisons across the literature are however limited by the substantial methodological variation across studies. Notable variations in data collection and analysis throughout the literature include testing posture (e.g., supine, sitting, or standing) and joint angle [ 5 , 21 , 23 ], testing equipment (i.e., computerized versus handheld dynamometer) [ 11 13 , 19 , 20 ], mode of muscle action (i.e., isometric versus isokinetic) [ 5 , 8 , 11 , 13 , 23 ], whether the prosthesis is worn [ 10 12 , 21 , 23 ] or removed [ 5 , 8 , 9 , 13 , 19 , 24 , 28 , 31 ] while testing the residual limb, gravity compensation, familiarization (i.e., number of trials) [ 55 ], and normalization for confounding anthropometric variables [ 22 ]. The adoption of standardized methods for data collection, processing, and reporting of strength-related outcomes in LLP users would enable the comparison and aggregation of data across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gait deviations [ 10 , 12 , 13 ], reduced walking speed and endurance [ 5 , 11 , 14 , 20 , 21 , 77 , 78 ], as well as increased metabolic cost [ 16 ] have historically been associated with weakness in the residual limb of unilateral LLP users. Several recent studies have however reported that intact limb muscle function may also play a substantial role in determining walking endurance [ 79 ] and physical activity levels [ 19 ] among unilateral LLP users. The results of these latter studies, and our discovery that once scaled to body size the intact not residual limb hip muscles appear weaker, injects uncertainty into whether walking and balance performance in unilateral LLP users is limited primarily by intact or residual limb muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 That said, physical activity after LLA is influenced by various factors. Previous research suggests, along with patient demographic (i.e., age, sex) and amputation-specific (i.e., amputation etiology, time since amputation) characteristics, 11 modifiable physiological factors, such as hip muscle strength 23 and functional mobility, 24 may play a significant role in determining physical activity. In addition, psychological factors, such as motivation and patient perceptions of their amputation and prosthesis, may influence overall physical activity after LLA.…”
Section: Discussionmentioning
confidence: 99%